1996
DOI: 10.1017/s0950268800001400
|View full text |Cite
|
Sign up to set email alerts
|

The application of genotyping techniques to the epidemiological analysis ofCampylobacter jejuni

Abstract: SUMMARYCampylobacter jejuni serogroup reference strains and collections of sporadic and outbreakassociated isolates were examined for restriction fragment length polymorphisms (RFLPs), using C. jejuni random chromosomal and 16S rRNA gene probes. A collection of 48 Penner (HS) and 14 Lior (HL) serogroup reference strains, plus 10 clinical isolates, generated 35 RFLP and 26 ribotype patterns. In combination the two loci generated 48 distinct genotypes. Both probes were able to differentiate between certain rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…PFGE typing of members of several serogroups identified by the Lior typing scheme has revealed little, if any, correlation (87,88). Similarly, identical ribopatterns can be obtained for members of multiple HL antigen serotypes (40).…”
Section: Comparison Of Genotypic and Phenotypic Subtyping Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…PFGE typing of members of several serogroups identified by the Lior typing scheme has revealed little, if any, correlation (87,88). Similarly, identical ribopatterns can be obtained for members of multiple HL antigen serotypes (40).…”
Section: Comparison Of Genotypic and Phenotypic Subtyping Methodsmentioning
confidence: 99%
“…C. jejuni serotype HS1, HS2, and HS4 isolates exhibited considerable genetic diversity within the serogroups as determined by both PFGE (28,73) and fla typing (9, 68) and, to a lesser extent, by ribotyping and RAPD analysis (20,28,40,73). A comparison of RAPD fingerprinting and HS antigen serotyping results suggested that sometimes there can be correlations between the data obtained with these two typing schemes (55); however, such correlations are unpredictable (1,36).…”
Section: Comparison Of Genotypic and Phenotypic Subtyping Methodsmentioning
confidence: 99%
See 3 more Smart Citations